Explaining globalization scepticism - Erik Lundsgaarde (Danish Institute for International Studies (DIIS), 2018)
This report examines explanations for scepticism towards economic globalization within and across countries, focusing on factors that help to situate the extent of globalization scepticism in Denmark alongside experiences in France and Germany. The report is based on a review of academic literature dealing with attitudes towards globalization and the linkages between globalization and national politics. Globalization is an umbrella term for a broad range of phenomena and has economic, political and cultural dimensions. The diverse expressions of globalization present a challenge when it comes to identifying sources of globalization scepticism because the latter may be directed at different targets, including multinational corporations or the national governments that influence how international economic integration is managed. In addition, perceived consequences of globalization may reflect other changes that are difficult to isolate from globalization, with technological development providing a prominent example. Many studies of individual attitudes towards economic globalization take the distribution of economic gains or losses due to free trade within societies as a starting point. In economies where highly skilled labour is abundant, benefits from free trade are likely to flow towards workers with a higher level of education while low-skilled workers may be disadvantaged. Certain sectors of economic activity may also be more exposed to competition from increasing international economic integration, leaving workers more vulnerable. Employment-related categories are not the only way of distinguishing winners and losers of globalization. For example, low-income consumers may benefit more from free trade than highincome consumers. Gains or losses from globalization may also vary by geographical location, depending on the nature of economic activity in different regions.
Keywords: 300